Formação e violência como fragmentos de memórias da docência - Pedroso, Eliana Regina Fritzen (2019)
This thesis work was developed within the Research Line Training, Knowledge and Professional Development (LP1), Postgraduate Program in Education, Center of Education, Federal University of Santa Maria-RS. The research consisted, centrally, in clarifying and dimensioning the “weight” and the meaning that violence assumes in human formation, especially in teacher education. To this end, we follow Walter Benjamin's studies, highlighting the research prominently by the contributions of the text To the Criticism of Violence, from which it is possible to understand that the way we most often encounter violence is mythic or law violence, whose most constant expression is given by the state in its control task. On the other hand, even in the Benjaminian perspective, divine violence has the role of purifying all the violence produced by law, manifesting itself in committed actions of claim for the change of situations of injustice. In this sense, it has, potentially, a reference in the sphere of education, through the action of critical thinking, expressed in mediating movements through the instance of language. Therefore, we propose to empirically inquire into the implications of the different manifestations and experiences of violence present in the teachers' memory. Under these conditions, our basic questions are stated in the following terms: How can the narratives emanating from teachers (through recollection) understood and organized in the methodological perspective of the Medieval Mosaic, offer possibilities for understanding the complex relationship between violence and formation? What memories does the teacher have about the violence in the school space of his / her student experience, and how does this issue, to some extent, relate to “being a teacher”? This means thinking about teacher education based on the importance that the category of violence exerts, through memory, in the trajectory of human formation marked by its schooling career. In this sense, this thesis adds specific contributions to the field of teacher education through the philosophy of education. Thus, we defend the thesis that the formation of the teaching being in its inextricable relation with the formative memory is constituted by violence; therefore, the remembrance and critical self-clarification of this process - together with the psychoanalytical bases - should be established as pillars for the formation and teaching performance in the non-violence instance.